THE SOCIAL DIMENSIONS OF A PERSON IN “THE RADICAL HUMANISM” OF E. FROMM - Фоменко, А. Н. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article it is analyzed the humanistic tends of philosophy of E. Fromm about the mechanisms of the persons’ individuality and standing of the «healthy society».